Reducing Phenolics Related to Bitterness in Table Olives - Rebecca L. Johnson; Alyson E. Mitchell (Journal of Food Quality)
Olives are one of the oldest food products in human civilization. Over the centuries, numerous methods have been developed to transform olives from a bitter drupe into an edible fruit. Methods of processing table olives rely on the acid, base, and/or enzymatic hydrolysis of bitter phenolic compounds naturally present in the fruit into nonbitter hydrolysis products. Today, there are three primary methods of commercial table olive processing: the Greek, Spanish, and Californian methods, in addition to several Artisanal methods. This review focuses on the technological, microbiological, chemical, and sensory aspects of table olive processing and the inherent benefits and drawbacks of each method. The table olive industry is facing challenges of environmental sustainability and increased consumer demand for healthier products. Herein, we examine current research on novel technologies that aim to address these issues.